A hol(e)y predicament. Issue 4 (20th April 2017) - Meka, Shaiva Ginoya; Shelden, Daniel; Mertens, Amy; Christensen, Paul; Patel, Meet
Abstract : Endocardial cushion defects are congenital abnormalities that result in valvular dysfunction as well as defects (or "holes") in the septa of the heart. They are typically diagnosed in early infancy; presentation late in life is rare. We present the case of a 72‐year‐old female admitted to the hospital with dyspnoea and palpitations. She was found to have multifocal atrial tachycardia. She suffered cardiac arrest associated with refractory hypoxaemia that required mechanical ventilation and vasodilator therapy with inhaled nitric oxide. Echocardiography revealed a large ostium primum atrial septal defect (ASD) complicated by Eisenmenger syndrome. It is likely that her arrhythmia, a sequela from her long‐standing congenital abnormality, led to sudden decompensation. In this case presentation, we review the aetiology, presentation, and complications of ASDs. Abstract : A 72‐year‐old female with tachycardia suffers a cardiac arrest associated with refractory hypoxaemia. She is found to have a large ostium primum atrial septal defect complicated by Eisenmenger syndrome. Late presentation of congenital heart defects and nitric oxide as a salvage therapy for persistent hypoxaemia are discussed.